Rearing and marketing of livestock in the Hakaluki Haor: Impact on livelihood, food and nutrition security - M. A. Hashem (Journal of Agriculture, Food and Environment)
The study aims at assessing and analyzing the core food security indicators to formulate policy option to improve food and nutrition security of the haor people. A survey was conducted using structured questionnaire covering 200 households in 2017. Socio-economic and demographic characteristics influence the production, income and consumption process of farm household. Average family size, literacy rate and dependency ratio were 6.45, 0.48 and 0.69, respectively. Average land area and income of the farm household were 250.62 decimal and BDT 246300.72 respectively. Total income increased notably with the increase in income from agriculture and livestock. The annual family expenditure increased significantly with the increase in food expenditure, land size andeducation. The yearly family expenditure was BDT 2,48,309. Farmers consumed 22 food items among which rice, potato; leafy vegetables, milk, meat and egg are the most important food items. Average daily per capita food, calorie and protein intake were 1172g, 2419 kcal and 86 g, respectively. Average daily per capita calorie and protein received from livestock and their products were 148.16 kcal and 16.62 g respectively. Average proteins from animal origin were 21.25 g of which fisheries contributed 22% andlivestock contributed 78%. Average HDDS was 11.85. Binary and multinomial logistic regressions suggested that food security decreased with the increase in family size and increased with the increase in weekly cost of all food items. Marketing and adoptingvalue chain by the farm households increased the income significantly. Absolute poverty was 33% and hard core poverty was 14% on the basis of DCI method. Absolute and hard core poverty were 29% and 20% respectively on the basis of CBN method. The major problems of the peoples were loss of assets due to natural calamities, high price of food items, improper marketing channels and inadequate supply of agricultural inputs. There are vast scope of utilizing land and water resources for ensuring food and nutrition security of livestock in the haor area. A package of policy options is suggested to increase food and nutrition security of the haor people.